2011
DOI: 10.1139/y11-034
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of peoniflorin against hydrogen peroxide-induced oxidative stress in human umbilical vein endothelial cells

Abstract: Peoniflorin (PF), extracted from the root of Paeonia lactiflora Pall., has been reported to have anti-inflammation and antioxidant effects in several animal models. Herein, we investigated the protective effects of PF against hydrogen peroxide (H(2)O(2))-induced oxidative damage in human umbilical vein endothelial cells (HUVECs). HUVECs were treated by H(2)O(2) (240 µmol/L) with or without PF. PF significantly increased the percent cell viability of HUVECs injured by H(2)O(2) using the 3-(4,5-dimethylthiazol-2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(29 citation statements)
references
References 36 publications
(36 reference statements)
0
29
0
Order By: Relevance
“…Besides, glycosides are the main ingredients of Paeoniae Radix Rubra. Paeoniflorin is a potent anti-inflammatory agent that can ameliorate the leukocyte infiltrates and adhesion molecules expression [38,39]. These data suggest that most herbs from TCM have a better therapeutic effect on inflammation.…”
Section: The Effects Of Herbs and Standards On Anti-gout In Vitromentioning
confidence: 90%
“…Besides, glycosides are the main ingredients of Paeoniae Radix Rubra. Paeoniflorin is a potent anti-inflammatory agent that can ameliorate the leukocyte infiltrates and adhesion molecules expression [38,39]. These data suggest that most herbs from TCM have a better therapeutic effect on inflammation.…”
Section: The Effects Of Herbs and Standards On Anti-gout In Vitromentioning
confidence: 90%
“…15,16) Thus, protection of endothelial cells from ROS-induced injury may therefore provide beneficial therapeutical intervention for successful treatment of cardiovascular diseases. 17) Salidroside, a major active ingredient exsiting naturally in R. rosea L., has been reported to be a strong antioxidant. In the present study, we demonstrated for the first time that salidroside was capable of protecting EVC-304 cells from oxidative stress and the accompanied apoptosis caused by endogenous H 2 O 2 .…”
Section: Discussionmentioning
confidence: 99%
“…PF has many biological activities and has been shown to be anti-inflammatory [2][3][4] , analgesic [5] , and an antioxidant [6,7] . Furthermore, PF is a potential neuroprotective agent.…”
Section: Introductionmentioning
confidence: 99%